Graphitic carbon nitride-based 2D catalysts for green energy: Physical mechanism and applications. (September 2020) - Kong, L.; Song, P.; Ma, F.; Sun, M.
Abstract: Graphite carbon nitride (g-C3 N4 ) has attracted more and more attention, because of its excellent band structure and thermochemical stability, and high efficiency on catalysis. In recent years, g-C3 N4 nanostructured photocatalysts have been applied to the fields of energy, environments, and g-C3 N4 with different surface morphology, electronic structure, and light absorption range has been widely studied in the field. In this review, we focus on the physical mechanism and summarize recent progress of efficient photocatalysts by adjusting the electronic structure and surface morphology of g-C3 N4 . Lastly, the challenges and opportunities of g-C3 N4 are prospected in the concluding remarks. Graphical abstract: Image 1 Highlights: Graphite carbon nitride (g-C3 N4 ) has attracted more and more attention, because of its excellent band structure and thermochemical stability, and high efficiency on catalysis. g-C3 N4 nanostructured photocatalysts have been applied to the fields of energy, environments, and g-C3 N4 with different surface morphology, electronic structure, and light absorption range has been widely studied in the field. We focus on the physical mechanism and summarize recent progress of efficient photocatalysts by adjusting the electronic structure and surface morphology of g-C3 N4 . The challenges and opportunities of g-C3 N4 are prospected in the concluding remarks.